Transparansi dan Akuntabilitas dalam Proses Rekrutmen Anggota Badan Permusyawaratan Desa (BPD) di Desa Simanungkalit Kabupaten Tapanuli Utara - Rosa Elfrida Sitompul; Wiro Oktavius Ginting (CV. Denasya Smart Publisher, 2026)
Transparency and accountability in the recruitment process of Village Consultative Body (BPD) members are essential elements in achieving good village governance. A recruitment process that lacks transparency and accountability may lead to low public participation, weak institutional legitimacy, and suboptimal oversight functions at the village level. In Simanungkalit Village, several issues remain, including limited access to information, uneven dissemination of recruitment information, and inadequate mechanisms of public accountability. This study aims to analyze the implementation of transparency and accountability in the recruitment process of BPD members in Simanungkalit Village, North Tapanuli Regency. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The analysis is based on transparency indicators proposed by Krina (2003:17), including clarity of information, accessibility of information, complaint mechanisms, and information dissemination, as well as accountability indicators proposed by David Halmer and Mark Turner (in Manggaukang Raba, 2006:115), which include legitimacy, moral quality, public responsiveness, policy transparency, optimal use of resources, and effectiveness and efficiency. The findings reveal that transparency in the recruitment process of BPD members in Simanungkalit Village has not been fully optimized, particularly in terms of information dissemination and accessibility, which has affected the level of public participation. Meanwhile, accountability has been implemented procedurally in accordance with existing regulations; however, it remains weak in substance, especially regarding information openness, documentation, and complaint mechanisms. Implementation of transparency and accountability in the recruitment of BPD members still requires improvement. Therefore, it is recommended to strengthen information dissemination systems, enhance public participation, and improve accountability mechanisms to ensure a more transparent, participatory, and accountable recruitment process in accordance with the principles of good governance.